Environmental Toxicology and Risk Assessment 1993
DOI: 10.1520/stp19246s
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and Histologic Changes in Brains of Great Blue Heron Hatchlings Exposed to PCDDs: Preliminary Analyses

Abstract: Throughout the United States and Canada the polychlorinated di-benzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) released in kraft pulp effluent have become a matter of intense public and regulatory concern. The central nervous system (CNS) is known to be one organ that is sensitive to environmental toxins. Although several studies have demonstrated biochemical changes in various regions of dioxin- and polychlorinated biphenyl (PCB)-exposed brains, no one has yet characterized the specific cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…In Apis mellifera , the right wings were shown to be larger than the left wings (Szentgyörgyi et al 2016) similar to the wings of Anthophora plumipes in our research. Directional asymmetry probably has a genetic basis (Palmer Bee size and asymmetry on a urban gradient 303 and Strobeck 1992) but environmental conditions may also contribute to it (Graham et al 1993;Henshel et al 1993;Lens and van Dongen 2000). Therefore it is possible to generate directional asymmetry by stressing an organism (Graham et al 1993;Hoffmann and Merilä 1999;Lens and Van Dongen 2000) even over a very short time period (Pélabon et al 2006).…”
Section: Modelmentioning
confidence: 99%
“…In Apis mellifera , the right wings were shown to be larger than the left wings (Szentgyörgyi et al 2016) similar to the wings of Anthophora plumipes in our research. Directional asymmetry probably has a genetic basis (Palmer Bee size and asymmetry on a urban gradient 303 and Strobeck 1992) but environmental conditions may also contribute to it (Graham et al 1993;Henshel et al 1993;Lens and van Dongen 2000). Therefore it is possible to generate directional asymmetry by stressing an organism (Graham et al 1993;Hoffmann and Merilä 1999;Lens and Van Dongen 2000) even over a very short time period (Pélabon et al 2006).…”
Section: Modelmentioning
confidence: 99%
“…Directional Asymmetry occurs when one side of a bilateral character is consistently larger than the other side (Van Valen 1962). Although DA is less associated with developmental stability (Palmer 1994), it has been found to differ between parents and their hybrid offspring (Auffray et al 1996; and transitions between FA and DA have been suggested as indicators of stress in populations (McKenzie and Clarke 1988;Graham et al 1993;Henshel et al 1993;Leamy et al 1999).…”
mentioning
confidence: 99%
“…Methods were as described in detail in Henshel et al (9). Briefly, two eggs from each nest were collected by the Canadian Wildlife Service.…”
Section: Methodsmentioning
confidence: 99%